Acetaminophen, ibuprofen, and tramadol analgesic interactions after adenotonsillectomy. Issue 10 (16th August 2018) - Hannam, Jacqueline A.; Anderson, Brian J.; Potts, Amanda
Summary: Background: The impact of tramadol in children given acetaminophen‐ibuprofen combination therapy is uncertain in acute pediatric pain management. A model describing the interaction between these three drugs would be useful to understand the role of supplemental analgesic therapy. Methods: Children undergoing tonsillectomy were given oral paracetamol and ibuprofen perioperatively. Blood was taken for paracetamol and ibuprofen drug assay on up to six occasions over 6 h after the initial dose. Tramadol was administered by caregivers for unacceptable postoperative pain. Pain was measured using the Parent's Postoperative Pain Measurement rating two hourly on the first postoperative day. A first‐order absorption, one‐compartment linear model with first‐order elimination was used to describe acetaminophen and ibuprofen disposition. Analgesia was described using an E MAX model extended for three drugs, assuming additive effects. Curve fitting was performed using nonlinear mixed effects models. Results: Pharmacodynamic parameter estimates, expressed using fractional Hill equation, were maximum effect ( E MAX ) 0.65 (95%CI 0.54, 0.74), the concentration of acetaminophen associated with 50% of the maximal drug effect (C50, ACET ) 7.06 (95%CI 7.03, 7.72) mg/L, and the ibuprofen C50 (C50, IBU ) 3.95 (95%CI 2.57, 7.53) mg/L. The Hill coefficient was 1.48 (95%CI 0.92, 2.62) and an interaction term was fixed at zero (additivity). The half‐time ( t 1/2 keo) for equilibration between the plasma and effect site was 0.34 hour (95%CI 0.23, 1.98) for acetaminophen and 1.04 hour (95%CI 0.75, 1.77) for ibuprofen. Tramadol had a C50, TRAM of 0.07 (95%CI 0.048, 1.07) mg/L with a t 1/2 keo, TRAM 1.78 hour (95%CI 1.06, 1.96). Conclusion: Ibuprofen has an EC50 for analgesia in children similar to that of adults (3.95 mg/L; 95%CI 2.57‐7.53, vs 5‐10 mg/L adults). The maximum effect from combination therapy (ie, 65% reduction in pain score) achieves satisfactory analgesia with commonly used doses but increased dose adds little additional benefit. The addition of tramadol to this analgesic mixture prolongs analgesia duration.